PENGARUH KESADARAN DIRI TERHADAP KEDISIPLINAN SISWA DI SMAN 2 TILATANG KAMANG - Ulfazila Afratul Islamy; Afrinaldi; Muhiddinnur Kamal; Fadhilla Yusri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study is based on real-world events: some students still have low awareness of the consequences of being late and wearing inappropriate uniforms, being late to class, playing with their phones while lessons are being taught, and eating while the teacher is teaching. In addition to these phenomena, there are also those related to self-awareness, namely there are still students who leave or jump over fences so that they do not participate in learning in class, do not realize when they have talents or interests in certain fields, depend on others when studying. Therefore, this phenomenon shows that students still lack self-awareness to comply with school regulations. The purpose of this study was to determine how much influence self-awareness has on student discipline in grades X and XI at SMAN 2 Tilatang Kamang. In addition, it is also to determine how much influence self-awareness has on student discipline in the class. This study used a quantitative correlational method. This study involved 147 students from grades X and XI. Probability sampling was used to take samples from 37 students. The tool used was a questionnaire distributed to 37 people who answered. After undergoing validity and reliability tests, all tools met the requirements. The data processing process includes changes, coding, scoring, and tabulation. The data analysis technique used is a simple linear regression test. The results of the study revealed that self-awareness affects a student's discipline and the magnitude of the influence of self-awareness on student discipline is 32.1%. This can be seen after knowing the influence of the two variables. Based on the analysis of the determination coefficient to determine how much influence self-awareness has on student discipline with R² of 0.321 shows that the proportion of the influence of the self-awareness variable is 32.1% while the rest (100-32.1) is 67.9% influenced by other variables not examined in this study.